Learn from History: Lessons from Early Modern Japanese Physics Experiment Textbooks - Takahashi, Hiroshi; Akabane, Akira; Shozawa, Jun; Tamaki, Toyomi (Scientia in educatione, 2017)
The aim of our study is to explore the early history of the education of physics experiments in the Meiji era of Japan (1868–1912). In this paper, we examine three Japanese physics experiment textbooks which were published during 1880s. One characteristic feature is that the most of the experiments could be performed using simple handmade apparatuses. We consider what can be learned from the ingenuity of physics education pioneers of the late 19th century.